PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN AKTIVITAS BELAJAR MAHASISWA PADA MATAKULIAH PENGEMBANGAN BAHAN AJAR - Widyaningrum, Diyah Ayu (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2016)
Based on observations in the course of learning development of teaching materials in IKIP Budi Utomo, an outline of the learning activities using a model presentation discussion.Discussions presentations that do not yet able to accommodate the activity of the students. Some students look sleepy, some even speak for themselves with their friends. So, we need the learning process interesting and fun through classroom action research (PTK) with the implementation of project-based learning. Classroom Action Research (PTK) aims to describe the increase in students' learning activities in the course material development through project-based learning. The approach used in this study is a qualitative approach. This type of research is the Classroom Action Research (PTK). PTK steps include planning, implementing action, observation, and evaluation / reflection. These measures were taken in each cycle. This study uses three cycles. Data obtained in the form of learning process and field notes taken from the observation sheet as well as the group's activities in the lessons learned from the observation sheet. Overall, students' learning activities increased from the first cycle of 69.03% to 86.03% in the second cycle. Students are able to carry out all stages of the project is well on the second cycle. Products produced in accordance with the demands of the curriculum.